Non-involutive constrained systems and Hamilton-Jacobi formalism - Bertin, M. C. [UNESP]; Pimentel, B. M. [UNESP]; Valcarcel, C. E. [UNESP] (Academic Press Inc. Elsevier B.V., 2008)
In this work we discuss the natural appearance of the Generalized Brackets in systems with non-involutive (equivalent to second class) constraints in the Hamilton-Jacobi formalism. We show how a consistent geometric interpretation of the integrability conditions leads to the reduction of degrees of freedom of these systems and, as consequence, naturally defines a dynamics in a reduced phase space. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Hamilton-Jacobi formalism; Constrained systems; Generalized Brackets